Influence of governance on the relationship between foreign banks penetration and banking stability - Zohrehvand, Azadeh; Ibrahim, Saifuzzaman; Habibullah, Muzafar Shah; Yusop, Zulkornain; Burhan, Nik Ahmad Sufian (Karachi, 2020)
Globalization that has started decades ago is one of the main factors of the influx of foreign banks. The presence of foreign banks in a host country can have many effects on its banking sectors. One of them is it could increase competition and force domestic bank to take additional risk which could lead to instability of the sector. On the other hand, foreign bank penetration can also be a source of stability. It can enhance financial stability by offering valuable diversification in services or absorbing shocks. Nonetheless, it is said that the impact of foreign banks’ penetration could be influenced by the presence of governance in the host country. This study aims to examine the impact of governance on the foreign bank penetration-stability relationship. We focus our analysis on 54 developing countries during the period 1998 to 2016. The results from a two-step system GMM support the market risk hypothesis that the penetration of foreign banks decreases the stability of the host banking sector. However, the presence of governance in the country may reduce the negative stability impact of the foreign banks’ penetration.